Pengaruh Lama Fermentasi Terhadap Kadar Alkohol Arak (Ballo’) di Kecamatan Binamu Kabupaten Jeneponto - Sulfi Upi Hasan; Fadillah Fadillah (Poltekkes Kemenkes Mataram, 2021)
Arak is one traditional drink types that is included in the alcoholic beverage class. It is obtained from fermented foods containing sugar. One of alcohol type that is tested for levels is ethanol. This is a transparent liquid that easily evaporates and mixes with water. One of the factors that affect ethanol content is the lenght of fermentation. This research aimed to know the lenght effect of fermentation on alcohol level of arak (Ballo’) at Binamu subdistrict of Jeneponto regency with variety of time namely 0, 1, 3, 5 until 7 days. This research is expected to be recommended to community about the suggested length of fermentation. Method of research was experimental using sample of fresh ballo’ that had distinctive and sweet smell. The result of research indicated that the length variant of fermentation for 0 day was 5,52%, 1 day was 9,81%, 3 days were 19,66%, 5 days were 21,15 % and 7 days were 18,92%. The obtained level achieved quality standard based on National Agency of Drug and Food Control (BPOM) No. 14/2016 and according to result of statistical test obtained, the fermentation lenght has a very significant effect on the ethanol content produced.